Mathematical Models for the Design of Electrical Machines - Dubas, Frédéric; Boughrara, Kamel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a comprehensive set of articles reflecting the latest advances and developments in mathematical modeling and the design of electrical machines for different applications. The main models discussed are based on the: i) Maxwell-Fourier method (i.e., the formal resolution of Maxwell's equations by using the separation of variables method and the Fourier's series in 2-D or 3-D with a quasi-Cartesian or polar coordinate system); ii) electrical, thermal and magnetic equivalent circuit; iii) hybrid model. In these different papers, the numerical method and the experimental tests have been used as comparisons or validations.